Reliability and correlation of the force-pro device and computer-assisted navigation system for measurement of acetabular cup position in total hip arthroplasty - Chaiyanun Vijittrakarnrung (2020)
© 2020 Surgical Technology International™. Introduction: Acetabular cup malposition is very common in total hip arthroplasty (THA) and is significantly associated with many serious postoperative complications, such as dislocation, wear and loosening, and decreased range of motion. To improve the accuracy of intraoperative assessment, we recently developed an innovative sensor-based navigation system (Force-PRO device) using an inertial measurement unit and a 3D-printed liner for acetabular cup measurement, and aimed to evaluate its reliability and correlate its accuracy with that of a computer-assisted navigation system (CANS). Design: Method-comparison study between the Force-PRO device and a standard CANS in a 1:1 pelvic bone model. Methods: The test-retest reliability of both the Force-PRO device and CANS, and agreement between the Force-PRO device and CANS, for the measurement of acetabular inclination and anteversion angles, were examined using 40 random acetabular cup positions. Statistical analysis was performed by using limits of agreement and intraclass correlation coefficient (ICC). Results: The mean differences in the inclination angle and anteversion angle in test-retest of the Force-PRO device were-0.43°±1.03° and-0.40°±0.78°, respectively. The mean differences in the inclination angle and anteversion angle between the Force-PRO device and CANS were 0.70°±0.94° and -0.10°±0.44°, respectively. Excellent reliability in the inclination and anteversion angles of the Force-PRO device and excellent agreement between the Force-PRO device and CANS were demonstrated, with ICC values of 0.994 and 0.997, and 0.993 and 0.999, respectively Conclusion: The Force-PRO device showed excellent reliability equivalent to CANS with excellent agreement in acetabular cup position measurement comparable to that with CANS. Future clinical studies will be needed to evaluate the efficacy of this device.